Rural extension: Volume 3: Training Concepts and Tools - Gerster-Bentaya, Maria; Hoffmann, Vivian (CTA / GTZ / Margraf / Universität Hohenheim, 2011)
Being a good adviser depends not only on knowledge, but also on the ability to use concepts, apply methods, organise your own work and aquire and express a certain attitude. This third volume provides comprehensive guidance and assistance in areas such as training concepts and tools, course outlines and modules. It will be of special interest to anyone involved in the training of extension workers.